Prospek Pengembangan Usahatani Jeruk Siam di Desa Pupuan Kecamatan Tegallalang Kabupaten Gianyar - RIANTARI, NI MADE ANGGA; WIDYANTARA, I WAYAN; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2016)
Abstract The Siam Citrus Farming Development Prospects in the Village of Pupuan, Tegallalang Sub-District, the Regency of Gianyar Indonesia is an agricultural country and it means that farming plays important thing for the overall national economy. It can be seen from the numbers of people who live and work in the agricultural sector or national products which come fromagriculture . Subagricultural sector consists of several sub-sectors , namely food sub-sector , horticulture , plantation , animal husbandry , fishery , and for estryas well as agricultural services . Horticultureis one of the sub-sectors that has huge potential to be developed as aregional and national economic growth . Horticultural crops include fruit trees , vegetables and flowers , which is mostly perishable but it is needed everyday in the fresh condition . Siam citrus is one of the horticultural crops that have good prospects for the development effort. The Gianyar Regency is the second largest citrus producerin the Province of Bali with a total production of 446,757 . Results of the study indicated that ; ( 1) Revenues from citrus farming in 2014 was  averagely of Rp 13,708,342.01 per hectare ; ( 2) The value of R/C Ration of Siam citrus farmin the village of Pupuan , Sub- District of Tegallalang , Gianyar in 2014 amounted to 1.39 ; ( 3) Constraints experienced by the Siam citrus farmers consisted of two factors , namely internal factors such aspest attack , and external factors such as the marketing of Siam citrus was still conducted through middlemen and lack of transportation facilities to market the production to traditional markets in order togain greater profits. Keywords: Revenues from Siam Citrus farming.